Video Youtube Hutan Kota sebagai Media Pembelajaran Tentang Pengetahuan Hutan Kota dan Vegetasinya Di Purworejo - Fajar Adinugraha (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
One of the topics that need to be understood as a student teacher candidate is the taxonomy and morphology of plants including the names of their species. Urban forests provide alternative learning resources that can be created in the form of videos. The video was uploaded on the Youtube channel to help learning during the pandemic, which reduces offline activities. It is hoped that making Urban Forest videos and uploading them to Youtube media will be a solution to urban forest concerns. The purposes of writing the article include: 1) identifying spermatophyta in the urban forest of Purworejo; 2) make an urban forest learning video; 3) analyze students' understanding of urban forests and their vegetation. The method used is urban forest exploration, making videos, as well as pre and post test designs by giving online test questions after watching the video. Making a forest video begins with identifying plants. There are 17 species used in making urban forest videos. The dominant vegetation in the Purworejo urban forest is acacia, teak, and mahogany. A learning video with a duration of 25 minutes 54 seconds uploaded on a personal Youtube channel, namely Fajar Adinugraha Channel with the link https://youtu.be/trPQ2yLBpWw. In its creation, the Pl@ntnet application was used to assist identification with the help of wikipedia. The application of learning videos via youtube was able to increase the score of 28.56 points from the pretest score so that there was a significant difference between the pretest and posttest scores for knowledge of urban forests and their vegetation.